2020
DOI: 10.1111/vsu.13501
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intra‐articular mepivacaine administration prior to carpal arthroscopy on anesthesia management and recovery characteristics in horses

Abstract: Objective: To evaluate the effects of intra-articular (IA) mepivacaine administration prior to carpal arthroscopy on anesthetic drug requirements, blood pressure support, hemodynamic variables, and quality of recovery in horses. Study design: Experimental, analytical, cohort study. Sample population: Twenty-two horses (n = 11 horses/group). Methods: Horses were anesthetized by using the same protocol, but an IA injection of mepivacaine or saline was performed before carpal arthroscopy. End-tidal isoflurane con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Other authors failed to identify a benefit in terms of QR when peripheral nerve blocks were performed prior to recovery 26,125 . Similarly, a group of researchers found no difference in QR in horses receiving either an intra‐articular injection of mepivacaine or saline performed before carpal arthroscopy 126 Although, in three of these studies, 125,126,128 the sample size was small which may hinder the ability to detect a difference between groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors failed to identify a benefit in terms of QR when peripheral nerve blocks were performed prior to recovery 26,125 . Similarly, a group of researchers found no difference in QR in horses receiving either an intra‐articular injection of mepivacaine or saline performed before carpal arthroscopy 126 Although, in three of these studies, 125,126,128 the sample size was small which may hinder the ability to detect a difference between groups.…”
Section: Resultsmentioning
confidence: 99%
“…A total of five studies were identified that assessed the effect of locoregional anaesthesia on QR (Table 8). The evidence presented regarding the impact of peripheral nerve blocks and intra‐articular opioid or local anaesthetic administration on QR is inconsistent 26,126,134 …”
Section: Resultsmentioning
confidence: 99%
“…(1) The effect of epidural xylazine on halothane minimum alveolar concentration in ponies [272] (2) Epidural morphine and detomidine decreases postoperative hindlimb lameness in horses after bilateral stifle arthroscopy [273] (3) Castration of horses under total intravenous anaesthesia: Analgesic effects of lidocaine [274] (4) Local mepivacaine before castration of horses under medetomidine isoflurane balanced anaesthesia is effective to reduce perioperative nociception and cytokine release [275] (5) Intratesticular mepivacaine versus lidocaine in anaesthetised horses undergoing Henderson castration [276] (6) The effect of intra-articular mepivacaine administration prior to carpal arthroscopy on anesthesia management and recovery characteristics in horses [277] 2 / 3 (7) Epidural administration of opioid analgesics improves quality of recovery in horses anaesthetised for treatment of hindlimb synovial sepsis [278] (8) Clinical assessment of an ipsilateral cervical spinal nerve block for prosthetic laryngoplasty in anesthetized horses [279] 4 (9) The outcome of epidural anaesthesia in horses with perineal and tail melanomas: Complications associated with ataxia and the risks of rope recovery [280] 5 / Total loco-regional publications = 9…”
Section: Loe and Topic Referencesmentioning
confidence: 99%
“…Nine publications focused on different loco-regional techniques [272][273][274][275][276][277][278][279][280]. In the last few years, a renaissance of loco-regional techniques on standing horses has occurred with the advent of ultrasound guided technology [469,470].…”
Section: Other Drugs Used During Maintenancementioning
confidence: 99%
See 1 more Smart Citation